Dez Anos da PNEEPEI: uma análise pela perspectiva da biopolítica - Pagni, Pedro Angelo (Universidade Federal do Rio Grande do Sul - Faculdade de Educação, 2019)
Abstract: Amid the uncertainty of the current political context and an unprecedented institutional crisis in Brazil, this essay offers a theoretical analysis of the problems arising from the drafting, implementation and setback of PNEEPEI from a biopolitical perspective. To this end, supported by analyses by Foucault and Agamben, we will understand how Brazilian state governmentality addresses the inclusion of people with disabilities in school in terms of both biopolitics and Thanatos-politics. In light of the criticism of the scientific paradigm that brings together these two aspects underpinning PNEEPEI, we propose an aesthetic paradigm of inclusion to better meet the demands of the ethos of these people in school.

Resumo: Em meio às incertezas do quadro político atual e de uma crise institucional sem precedentes no Brasil, este ensaio analisa teoricamente os problemas decorrentes da elaboração, implantação e dos refluxos da PNEEPEI pela perspectiva da biopolítica. Para isso, apoiados nas análises de Foucault e Agamben, compreenderemos o modo como a governamentalidade estatal brasileira se ocupa da inclusão das pessoas com deficiência na escola, elucidando suas faces tanto biopolítica quanto tanatopolítica. À luz da crítica ao paradigma científico que congrega essas faces, no qual a PNEEPEI se apoia, propomos um paradigma estético de inclusão, com vistas a melhor atender as demandas do ethos dessas pessoas na escola.
Ten Years of PNEEPEI: an analysis from a biopolitical perspective
Keywords: Biopolitics; Inclusion; Disability; PNEEPEI; Aesthetic Paradigm; Biopolítica; Inclusão; Deficiência; PNEEPEI; Paradigma Estético